PENGARUH LATIHAN SENAM AEROBIK TERHADAP PENURUNAN BERAT BADAN, PERSENTASE LEMAK TUBUH DAN PENINGKATAN MASSA OTOT - siska zamhar bakri (Jurnal Sporta Saintika, 2020)
This study aims to reveal 1) The effect of aerobic exercise on weight loss 2) The effect of aerobic exercise on the proportion of fat body, and 3) the effect of aerobic exercise or increasing muscle mass. This research uses quasi-experimental (quasi-experiment). The population is all members of the gymnastics fit club Simpang D Rokan Hulu Regency, with a sample of 10 people. The sampling technique was carried out by total sampling with a total of 10 people. The research instruments for obtaining data were: (1) Tanita BC-541 innerscan digital body scale to measure body weight, (2) skin fold calipers to measure body proportions and (3) Tanita BC-541 innerscan digital body scale for body composition to measure body weight. measure muscle mass. The data analysis technique used is the t test. The results and data analysis showed that: (1) Aerobic exercise had a significant effect on weight loss tcoun 2.186> ttable 1.782. The average value of pretest is 66.86 kg and posttest is 66.12 kg. there was a decrease of 0.74 kg. (2) Aerobic exercise has a significant effect on decreasing the proportion of the body tcount 3.285> ttable 1.782. The average pretest score was 40.45% and posttest 37.18%, there was a decrease of 3.27%. (3) Aerobic exercise has a significant effect on muscle mass tcount 1,835> table 1,782. The pretest means score was 37.72 and posttest 37.63, there was a decrease of 0.09